Qualidade de vida de idosos hipertensos e/ou diabéticos acompanhados na atenção primária em saúde - Santos, Kalina de Lima (2018)
This work sought to analyze and to understand life‟s quality of elderly with systemic blood pressure and type II diabetes mellitus in the primary attention of health of the city of Campina Grande - PB. It was a transversal descriptive and exploratory research with quantitative and qualitative characteristics in a multi-method approach. For acquisition quantitative data , the following instruments were used: Sociodemographic questionnaire for characterization of the sample and a question about elderly having systemic blood pressure and/or type II diabetes mellitus, proved by the Basic Health Unit (UBS); the quality of life scale WHOQOL-bref, that evaluated the quality of life of the participants; e the Mini Examination of Mental State (MEEM), a cognitive tracing test, which guaranteed the choice of preserved cognition‟s participants, for attainment of the data. From 508 of those surveyed, 371 were identified as carrying systemic blood pressure and/or type II diabetes mellitus, monitored at a UBS. According to convenience and accessibility criteria, 13 elderly formed two focal groups, technique used to get qualitative strategy data. Descriptive statistical analyses (averages, standard deviat ions and amplitude) were made based on the data bank built, for the treatment of the sociodemographic data and life quality score, and cross-check dependent and independent variables to verify whether there was association between them. The data collected by means of qualitative strategy – from the focal groups, were codified by the analysis of thematic content. The bred categories were inserted in the software QDA miner with the corpus of the research, which helped to analyze quantitatively the sum of frequencies and percentages of classes of the categories. The results are presented in two articles, the first study possible to know relative important aspects to the quality of life and the characteristics associates, as income, presence of hypertension and/or diabetes mellitus, arrangement of housing and age. The results of article 2 had disclosed that the conceptions of quality of life of aged carriers of hypertension and diabetes mellitus pass for the process of living with the chronic illness, they point with respect to the relevance of questions of subjective order and call to the attention for the necessity to understand the relation of the aged one with its illness and to elaborate more assertive strategies of care. One concludes that the studies in que stion if add to the studies of the area of the Psychology of the Health, that considers the understanding of aspects of the health in the field of the not mental illnesses and considers two common illnesses in the day the day of the aged population: systemic arterial hypertension and diabetes mellitus of type II, that they can bring significant damages if they will not be controlled duly and if they configure as one of the challenges of the health services, over all considering the aged public.